Replacement name for Alishania Bickel, 2004 (Diptera Dolichopodidae) - Bickel, Daniel J. (Zootaxa, 2007)
Alishania Bickel, 2004 was proposed for a single species, A. elmohardyi, from Taiwan. At the time, a search of the Nomenclator Zoologicus and the Zoological Record did not reveal this name to be preoccupied, and the Vilbaste paper appears to have been overlooked by both references. However, I was kindly informed that Alishania is preoccupied by Vilbaste, 1969 for a Homoptera genus, also from Taiwan. As these names are homonyms, Alishanimyia is proposed as a replacement name for Alishania Bickel 2004.